2012
DOI: 10.1016/s0377-1237(11)60128-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and catecholamine levels in sleep apnoea

Abstract: BACKGROUNDSleep-disordered breathing has been strongly associated with systemic hypertension. Increased sympathetic activity in sleep-disordered breathing may be responsible for this association. METHODIn this sleep clinic-based study, 82 newly diagnosed patients of sleepdisordered breathing were evaluated for hypertension, and their plasma and urinary levels of catecholamines were measured. Catecholamine levels were then compared separately with the severity of sleep apnoea and blood pressure (BP). RESULTSThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Diastolic dysfunction due to cardiac remodeling owing to the intravascular volume expansion among the obese could be a possible explanation for the higher prevalence of congestive heart failure among the obese TCM group . Obesity is also often associated with obstructive sleep apnea, and obstructive sleep apnea has been associated with high catecholamine levels . Increase in catecholamine levels is one of the most accepted pathogenic mechanisms in TCM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diastolic dysfunction due to cardiac remodeling owing to the intravascular volume expansion among the obese could be a possible explanation for the higher prevalence of congestive heart failure among the obese TCM group . Obesity is also often associated with obstructive sleep apnea, and obstructive sleep apnea has been associated with high catecholamine levels . Increase in catecholamine levels is one of the most accepted pathogenic mechanisms in TCM .…”
Section: Discussionmentioning
confidence: 99%
“…19 Obesity is also often associated with obstructive sleep apnea, and obstructive sleep apnea has been associated with high catecholamine levels. 20 Increase in catecholamine levels is one of the most accepted pathogenic mechanisms in TCM. 21 Overall, an excellent long-term prognosis of the disease with the recovery of the LV dysfunction within the few weeks could be a potential reason for the lower and nonsignificant difference in the in-hospital all-cause mortality, LOS, and hospitalization charges, despite higher complications among the obese TCM.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In the current study, we found increased 24-hour urinary norepinephrine was independently and significantly associated with elevated blood pressure in patients with OSA, which was consistent with previous findings. 22 However, this relationship was evident only in normal-weight, but not in overweight/obese patients with OSA.…”
Section: Discussionmentioning
confidence: 98%
“…Strengths of our study include the measurement of sympathetic drive using 24-hour urinary norepinephrine. Because the norepinephrine levels are easily influenced by stress, and their moment-to-moment variation is great due to the very short half-life in plasma (only 2 to 3 minutes), 22 , 47 we used 24-hour urinary norepinephrine to assess overall systemic sympathetic drive, rather than use a single measurement of plasma norepinephrine or the direct measurement of sympathetic nerve traffic via microneurography. Furthermore, compared to the direct measurement of sympathetic nerve traffic via microneurography, 24-hour urinary norepinephrine is a noninvasive, convenient and easy operative measure in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The observed microcirculatory changes were small, despite high OSA severity (median AHI 64.5). Catecholamine levels were found to be related to OSA severity [ 26 ]. Dose dependent vasoconstrictive effect of both epinephrine and norepinephrine is known [ 27 ].…”
Section: Discussionmentioning
confidence: 99%